2020
DOI: 10.1080/0163853x.2019.1700760
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Discourse Connectives Is Probabilistic: Evidence From the Study of But and Although

Abstract: Connectives can facilitate the processing of discourse relations by helping comprehenders to infer the intended coherence relation holding between two text spans. Previous experimental studies have focused on pairs of connectives that are very different from one another to be able to compare and formalize the distinguishing effects of these particles in discourse comprehension. In this article, we compare two connectives, but and although, which overlap in terms of the relations they can signal. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…It has also been shown that surprisal is linked with linguistic choice, low vs. high surprisal being correlated with reduced vs. fully expanded linguistic forms (Aylett and Turk, 2004;Levy, 2008;Mahowald et al, 2013). This holds across linguistic levels, from the phonetic to the grammatical and the discourse level (Delogu et al, 2017;Lemke et al, 2017;Sikos et al, 2017;Malisz et al, 2018;Asr and Demberg, 2020).…”
Section: Predictability and Uncertainty In Human Language Processingmentioning
confidence: 95%
“…It has also been shown that surprisal is linked with linguistic choice, low vs. high surprisal being correlated with reduced vs. fully expanded linguistic forms (Aylett and Turk, 2004;Levy, 2008;Mahowald et al, 2013). This holds across linguistic levels, from the phonetic to the grammatical and the discourse level (Delogu et al, 2017;Lemke et al, 2017;Sikos et al, 2017;Malisz et al, 2018;Asr and Demberg, 2020).…”
Section: Predictability and Uncertainty In Human Language Processingmentioning
confidence: 95%
“…Listeners predict upcoming material, such as the content of the following clause, based on the connective. Material is read slower (Asr & Demberg, 2020; Canestrelli et al, 2013; Scholman et al, 2017) or yields different brain responses (Köhne-Fuetterer et al, 2021; Xiang & Kuperberg, 2015) when it is not expected based on the connective. This is also reflected in faster reading times of clauses following a connective, compared to when no connective is present (Sanders & Noordman, 2000; van Silfhout et al, 2015) or an inappropriate connective is used (Canestrelli et al, 2013; Xu et al, 2018).…”
Section: The Effect Of Discourse Relational Cuesmentioning
confidence: 99%
“…For instance, the frequency of a connective in language use or its restriction to formal registers can make it less accessible for readers with low exposure to print (Zufferey and Gygax, 2020) and can cause immediate processing delays (Zufferey et al, 2018). In addition, when connectives can express multiple relations (e.g., but in contrast or concession, since in temporal or causal relations), comprehenders tend to be biased toward their most frequent meaning, while the secondary use is rated lower and read more slowly (Asr and Demberg, 2020). Similarly, the connective and can be found in many different discourse relations in corpora (Prasad et al, 2018) and in production data (Koornneef and Sanders, 2013).…”
Section: Processing Instructions For Discourse Relationsmentioning
confidence: 99%